2020
DOI: 10.1002/est2.133
|View full text |Cite
|
Sign up to set email alerts
|

High energy density of multivalent glass‐ceramic cathodes for Li‐ion rechargeable cells and as an efficient photocatalyst for organic degradation

Abstract: The tavorite-structured materials remain unfathomed as positive electrodes in rechargeable batteries. Reasoning of this fact, borate, and silicate-based tavorites are investigated for utilization in Li-ion batteries (LIBs) and as a photocatalyst for organic contaminant degradation. The physiochemical, electrochemical, dielectric, and photoelectrochemical properties are analyzed to learn the fact that LiVBO 4 F has resulted in a glass-ceramic nature owing to the embodiment of boron oxyfluoride glasses. This nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…On the other hand, Li 2 TP shows the spectacles bond length ranges between 1.7 to 3.25 Å confirming the ionic nature. This result discloses the covalent nature of −OH bonds from TPA is converted into the ionic nature of −O−Li (1.8709 Å) bonds [51] . Computationally measured bond lengths of individual atoms of TPA and Li 2 TP are provided in Table S1.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…On the other hand, Li 2 TP shows the spectacles bond length ranges between 1.7 to 3.25 Å confirming the ionic nature. This result discloses the covalent nature of −OH bonds from TPA is converted into the ionic nature of −O−Li (1.8709 Å) bonds [51] . Computationally measured bond lengths of individual atoms of TPA and Li 2 TP are provided in Table S1.…”
Section: Resultsmentioning
confidence: 55%
“…This result discloses the covalent nature of À OH bonds from TPA is converted into the ionic nature of À OÀ Li (1.8709 Å) bonds. [51] Computationally measured bond lengths of individual atoms of TPA and Li 2 TP are provided in Table S1.…”
Section: Charge-discharge Mechanism With Dft Simulationsmentioning
confidence: 99%
“…Increasing the operating voltage of ASCs via the development of metal-ion hybrid battery capacitors (MHCs) consisting of a capacitor-type cathode and a battery-type anode (such as Li-, K-, Na-, or Zn-metal) is considered an effective strategy to improve the overall energy density. [10][11][12][13][14][15] Among the various MHCs, aqueous Zn-ion hybrid capacitors (ZHCs) are the most promising owing to the abundant natural resources of Zn metal, high theoretical capacity (820 mA h g −1 ), lower redox potential (than normal hydrogen electrodes), outstanding safety, and environmental benignity. [16][17][18][19][20][21] Particularly, studies have demonstrated the simplicity and economic viability of ZHCs composed of activated porous carbon (PC) as a cathode, Zn foil as an anode, and aqueous Zn-electrolyte for energy storage via adsorption/desorption (ads/des), deposition/stripping and precipitation/dissolution mechanisms, respectively.…”
Section: Introductionmentioning
confidence: 99%